2021
DOI: 10.22437/bio.v7i3.14386
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara High Order Thinking Skills dan Kemampuan Literasi Sains Mahasiswa Pendidikan Biologi

Abstract: Higher Order Thinking Skills can develop the ability to investigate problems, ask questions, pose challenging answers and discover new information. Higher order thinking skills are one of the factors that affect scientific literacy skills. Literacy skills are not enough just to be able to read, more than that, students are expected to have the ability to reason and competence, be active, creative, and critical of what they know. The purpose of this study was to analyze the relationship between higher order thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
2
0
1
Order By: Relevance
“…The percentage is 7.9%, meaning that the influence of scientific literacy skills on HOTS is 7.9%, while other factors cause 92.1%. This is also the previous theory by Thahir (2021), mentioning that the ability of scientific literacy is included in science learning. Meanwhile, learning science can develop creativity, think critically, be a good citizen, and be aware of a broad career.…”
Section: Figure 1 Sobel Test Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The percentage is 7.9%, meaning that the influence of scientific literacy skills on HOTS is 7.9%, while other factors cause 92.1%. This is also the previous theory by Thahir (2021), mentioning that the ability of scientific literacy is included in science learning. Meanwhile, learning science can develop creativity, think critically, be a good citizen, and be aware of a broad career.…”
Section: Figure 1 Sobel Test Resultssupporting
confidence: 67%
“…Meanwhile, learning science can develop creativity, think critically, be a good citizen, and be aware of a broad career. Therefore, it can be concluded that learning science can lead to scientific literacy skills and have implications for higher order thinking skills and problem-solving (Thahir et al, 2021).…”
Section: Figure 1 Sobel Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literasi sains, atau kemampuan menerapkan dan menyampaikan sains, merupakan nama lain dari keterampilan pemecahan masalah yang muncul dari pemahaman sains. Kemampuan berpikir tingkat tinggi mungkin menyoroti perlunya membantu siswa menjadi melek sains (Thahir et al, 2021). Tujuan pendidikan sains saat ini adalah untuk membekali siswa dengan keterampilan yang mereka perlukan agar berhasil di Abad ke-21.…”
Section: Iunclassified